REVITALISASI PERPUSATAAN DESA DALAM MENDUKUNG MINAT LITERASI DI DESA MAJASARI KECAMATAN JAWILAN KABUPATEN SERANG - Rizky Esaputri; Muhammad Septiandi; Lingga Nabila; Alvi Afrianti; Gabriela Fernanda Sedubun; Ayati Ayati; Keanu Zimran; Siti Hojijah; Berliando Berliando; Muhammad Vhikry Salam; Chairunnisa Chairunnisa; Niesrina Nabihatul Huwaidah; Fachrul Riza (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to revitalize the village library so that it can function again as a center of literacy and learning for the community. The main problem encountered is the suboptimal management and utilization of village library facilities. The program was carried out at the Majasari Village Library, Jawilan Subdistrict, Serang Regency, using a participatory mentoring approach implemented through several stages: (1) Sorting library materials, (2) Applying ownership and inventory stamps, (3) Creating a master catalog book, (4) Preparing descriptive and subject catalogs, (5) Attaching labels, pockets, and book cards, and (6) Organizing collections according to categories. The results show that the library materials became more organized, the number of collections was well recorded, and the process of finding materials needed by the community became easier. This revitalization effort also contributes to strengthening literacy development within the village community.Keywords: Literacy; Jawilan; Village Library; Revitalization